2004
DOI: 10.1080/13547500400018281
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-immunoassay for the determination of metallothionein in human urine: application to environmental monitoring

Abstract: The objectives of this study were to develop an enzyme immunoassay for metallothioneins in human urine using a polyclonal antiserum and to demonstrate a possible relationship between the level of this biomarker and heavy metal exposure. The antiserum was raised in sheep against horse metallothionein conjugated to carboxylated bovine serum albumin. The antibody was used to construct a two-step competitive ELISA procedure. Human urine was treated with activated charcoal powder to remove traces of metallothionein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Direct, indirect, competitive, sandwich and multiplex types of the assays have been used. ELISA has been applied for MT determination is number of samples including hepatic cell lines [35], Sertoli cells of rats exposed to cadmium [36][37][38] and urine of children living in polluted environment [39]. The investigation of relationships between MT level and tumor diseases has shown down regulation of MTs in thyroid carcinoma [40] and MT overexpression in oral squamous cell carcinoma [41], in hepatocellular carcinoma [42] and also in laryngeal carcinoma [43].…”
Section: Immunochemical Methodsmentioning
confidence: 99%
“…Direct, indirect, competitive, sandwich and multiplex types of the assays have been used. ELISA has been applied for MT determination is number of samples including hepatic cell lines [35], Sertoli cells of rats exposed to cadmium [36][37][38] and urine of children living in polluted environment [39]. The investigation of relationships between MT level and tumor diseases has shown down regulation of MTs in thyroid carcinoma [40] and MT overexpression in oral squamous cell carcinoma [41], in hepatocellular carcinoma [42] and also in laryngeal carcinoma [43].…”
Section: Immunochemical Methodsmentioning
confidence: 99%
“…Investigations performed by Nordberg et al (1982) using radioimmunoassay showed that MT concentrations in plasma and urine ranged between 2-11.3 ng/g of protein and 2-155.2 ng/g of protein, respectively. MT levels were measured by a two-step competitive ELISA procedure in urine of two groups of children living in areas of mild and high environmental pollution due mainly to heavy metals (Swierzcek et al, 2004). The MT concentrations in that study ranged between 3-30 µg/g of creatinine.…”
mentioning
confidence: 86%
“…Considering heavy metal detoxification significance of MTs, these proteins can serve as biomarker of heavy metal pollution of the environment [12][13][14][15]. On the other hand, a comparison between the content of heavy metals and determined MTs could be very useful not only from ecotoxicological aspects but also from biochemical aspects due to the better understanding of different functions of MTs in an organism [16].…”
mentioning
confidence: 99%